PROFILE OF EPILEPSY PATIENTS IN PEDIATRIC WARD AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA IN THE PERIOD OF JANUARY-DECEMBER 2017 - Dewi Sekarsari; Viskasari P. Kalanjati; Abdulloh Machin; Prastiya I. Gunawan (Majalah Biomorfologi, 2020)
Background: Various risk factors of epilepsy in children had been reported although differences were found amongst regions. Objective: To identify the profile of epilepsy patients and previous febrile seizure history in children aged 0-17 years at Pediatric Ward, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2017. Materials and Methods: This was a cross-sectional retrospective study, using secondary data from medical records of epilepsy patients with febrile seizure history in children aged 0-17 years old at Pediatric Ward, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in the period of January-December 2017. Data analysis was done using t-test and Chi- Square test (Microsoft Excel 2007 and SPSS 22). The level of significance was p<0.05. Results: Seventy-four male and 38 female patients were included. Febrile seizure history was observed in 42 patients and there was no significant difference between febrile seizure history and prevalence of epilepsy. The general type of seizure was found in 79 patients; mostly from Surabaya, Indonesia and the parents’ occupation was private employee. The most observed type of seizure was general type. Conclusion: In this study, epilepsy was predominantly found in males than females; and a significant number of the patients were without febrile seizure history. General type of seizure was the most common type amongst others. These patients were mostly from Surabaya, Indonesia, whose parents' occupation was private employees.